(untitled) (Journal of Applied Oral Science, 2009)
OBJECTIVE: This study was designed to investigate the subjective ratings of dental anxiety levels among university students enrolled at Jordan University of Science and Technology. In addition, the present study aimed to explore the sources of dental anxiety and the impact of gender on the perceived dental anxiety and the correlation between field of study and dental anxiety level. MATERIAL AND METHODS: The Modified Corah Dental Anxiety Scale was used to measure dental anxiety among the study population. Six hundred subjects were recruited into the study from Jordanian undergraduate students from the faculties of Medicine, Engineering, and Dentistry. RESULTS: Five hundred and thirty five complete questionnaires were returned, which accounts for a response rate of 89.2%. The totals of the mean anxiety scores were the following: Medical students, 13.58%; Engineering students, 13.27% and dental students, 11.22%. About 32% of the study population has scored 15 or more. Dental students had the lowest percentage of those who scored 15 or more. Surprisingly, the medical students were responsible for the highest percentage of those who scored 15 or above. Although women demonstrated statistically higher total dental anxiety scores than men (p= 0.03), the difference between both genders was small and could be clinically insignificant. The students were anxious mostly about tooth drilling and local anesthetic injection. CONCLUSIONS: Lack of adequate dental health education may result in a high level of dental anxiety among non-dental university students in Jordan. Further studies are required to identify the correlates of dental anxiety among university students.